Randomized exploratory study to measure ion release from calcium sodium phosphosilicate‐containing dentifrice. (2nd August 2018) - Burnett, Gary R.; Morrison, Joanna; Whitworth, Darren; Hughes, Alison J.; Nehme, Marc; Sanyal, Susmita; Brotherhood, Andrew J.; Hall, Peter J.
Abstract : This exploratory study investigated salivary concentrations of silicon, calcium, sodium, and phosphorous over a 60‐min time period following the use of a calcium sodium phosphosilicate (CSPS)‐containing dentifrice. Participants brushed with a dentifrice containing 5% (w/w) or 0% (w/w) CSPS or swilled with a slurry containing 5% (w/w) CSPS/glycerol. Saliva samples were collected before, and 2, 5, 15, and 60 min after, product use and were analysed using inductively coupled plasma optical emission spectroscopy. Intra‐oral pH measurements were also taken. Primary analysis was of centrifuged saliva supernatant containing only dissolved material. At most time points, the CSPS‐containing dentifrice and slurry generated significantly more salivary silicon than the dentifrice containing 0% CSPS. At 2–15 min after brushing there was significantly more salivary calcium after use of the CSPS‐containing dentifrice and slurry, compared with the 0% CSPS dentifrice; a significant reduction, from baseline, in salivary calcium after use of dentifrice containing 0% CSPS; and an increase in salivary sodium after use of dentifrices containing either 5% or 0% CSPS, but no differences between them. Salivary phosphorous concentration decreased significantly with all treatments 2–5 min after use. There were no significant between‐treatment differences in intra‐oral pH. Products were generally well tolerated. This study establishes that it is possible to measure changes in salivary ionic composition derived through oral retention of CSPS, delivered via a dentifrice.